Key Competencies of Human Resource Capabilities in Hospitality Industry - Zairil, Zairil; Elmi, Farida (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research aims to examine the effect of competency on the capabilities of human resources in the hospitality industry. This study uses quantitative methods and uses 100 samples from various levels of positions in 3 - 5 star hotels and exhibition buildings. Researcher distributed questionnaires through an online system to hotels and exhibition buildings. Testing the validity and reliability of the research instrument was analysed using SmartPLS 3.0. The results showed that the use of common sense, quick response, communication and relationship skills are the main keys of competency and have a positive and significant effect on the ability of human resources. This research is expected to provide input to the hotel industry players in developing the right aspects of competency in increasing the capabilities of human resources in the hospitality industry. Lifestyle changes and high guest expectations require a quick response from employees and the ability to build relationships. Hotel management must continue to seek and transform in following the emerging trends in the market to be developed into employee development programs.